Biomarker-based diagnostic work-up of invasive pulmonary aspergillosis in immunocompromised paediatric patients - is Aspergillus PCR appropriate? - Buchheidt, Dieter; Reinwald, Mark; Spiess, Birgit; Boch, Tobias; Hofmann, Wolf-Karsten (Mycoses, 2016)
Invasive aspergillosis (IA) is an important cause of morbidity and mortality in children and adults with haematologic malignancies or undergoing allogeneic haematopoietic stem cell transplantation, and early diagnosis and adequate antifungal treatment improve outcome. However, important differences exist between children and adults regarding epidemiology, underlying disease, and comorbidities, and the value of diagnostic tools to detect IA may also differ between these patient populations. Imaging studies are important to detect IA early, but typical findings of IA in chest computed tomography of adults are not detected in the majority of children. Whereas the value of the serum marker galactomannan seems to be comparable in children and adults, data on the performance of beta-d-glucan in children are too limited for firm conclusions. PCR-based assays are a promising diagnostic approach to rapidly and reliably detect and identify Aspergillus species in various clinical samples. However, as the majority of data on PCR-based approaches has been obtained in adult patients, the value of this method in paediatric patients has not been defined to date. The present review focuses on studies of PCR-based methods to diagnose IA in immunocompromised paediatric patients.
Gesehen am 24.01.2019
First published: 14 December 2015